Study Some New Metallic Coordination Complexes and their Antibacterial Activity Against Methicillin- Resistant Staphylococcus Aureus - Nevein Nasser Abotreek; Mohammed Ahmed Awad (Indian Journal of Forensic Medicine & Toxicology, 2022)
The ligands were prepared by condensing aldehydes with aromatic amines, then they were held together with Ruthenium element Ru (III) and gold Au (III). Spectroscopic studies were conducted on them and demonstrated that the gold complex was a good conductor opposite to the ruthenium complex depending on its molar conductivity value. The complex was described by measuring the spectrum of FT. IR (C. MASS JV-VISIBLE and C.H.N). From spectroscopic data, the octahedral geometry of the ruthenium and Square Berner complex has been proposed for the gold ligands nodes. Furthermore, ligands and complexes have been selected for the activity of the methicillin-resistant golden cluster bacterium and the study of gene expression, i.e., the impact of ingested substances on RNA bacteria (MAR).